2021
DOI: 10.1186/s13722-021-00240-y
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating rapid access to addiction treatment: a randomized controlled trial

Abstract: Background Obtaining timely access to addiction medicine treatment for patients with substance use disorders is challenging and patients often have to navigate complex referral pathways. This randomized controlled trial examines the effect of providing an expedited pathway to addiction medicine treatment on initial treatment engagement and health care utilization. Methods Individuals with possible alcohol or opioid use disorder were recruited from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These results contribute to increasing evidence of the effectiveness of rapid access care models, particularly the impact on reducing acute health care use. Srivastava et al 31 conducted a randomized clinical trial of individuals with POU or PAU residing in withdrawal management services. Individuals in the rapid intervention group (ie, those given an appointment at an addiction medicine clinic within 2 days) had fewer ED visits in the 6 months after their referral compared with individuals in the delayed intervention group (ie, those given contact information for the addiction medicine clinic).…”
Section: Discussionmentioning
confidence: 99%
“…These results contribute to increasing evidence of the effectiveness of rapid access care models, particularly the impact on reducing acute health care use. Srivastava et al 31 conducted a randomized clinical trial of individuals with POU or PAU residing in withdrawal management services. Individuals in the rapid intervention group (ie, those given an appointment at an addiction medicine clinic within 2 days) had fewer ED visits in the 6 months after their referral compared with individuals in the delayed intervention group (ie, those given contact information for the addiction medicine clinic).…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of 440 client charts showed a high treatment retention rate at 1 year and high levels of client satisfaction 75 . Community access to OAT can also be improved through low-barrier strategies such as rapid access clinics and mobile clinics 76,77 …”
Section: Methodsmentioning
confidence: 99%
“…75 Community access to OAT can also be improved through low-barrier strategies such as rapid access clinics and mobile clinics. 76,77 OAT retention rates and outcomes can also be improved by providing wrap-around services include primary care, case management, and counselling. In a qualitative study of patients attending three Safer Supply programs in Ontario, patients reported greater access to primary care, improved management of chronic disease, improved income, and less food and housing insecurity.…”
Section: Strategies To Increase Access To Oat and Improve Treatment R...mentioning
confidence: 99%